Expression of the Fatty Acid Receptors GPR84 and GPR120 and Cytodifferentiation of Epithelial Cells in the Gastric Mucosa of Mouse Pups in the Course of Dietary Transition - Widmayer, Patricia; Kusumakshi, Soumya; Hägele, Franziska A.; Boehm, Ulrich; Breer, Heinz (Frontiers in Physiology, 2017)
During weaning, the ingested food of mouse pups changes from exclusively milk to solid food. In contrast to the protein- and carbohydrate-rich solid food, high fat milk is characterized primarily by fatty acids of medium chain length particularly important for the suckling pups. Therefore, it seems conceivable that the stomach mucosa may be specialized for detecting these important nutrients during the suckling phase. Here, we analyzed the expression of the G protein coupled receptors GPR84 and GPR120 (FFAR4), which are considered to be receptors for medium and long chain fatty acids, respectively. We found that the mRNA levels for GPR84 and GPR120 were high during the suckling period and progressively decreased in the course of weaning. Visualization of the receptor-expressing cells in two-week-old mice revealed a high number of labeled cells, which reside in the apical as well as in the basal region of the gastric glands. At the base of the gastric glands, all GPR84-immunoreactive cells and some of the GPR120-positive cells also expressed chromogranin A (CgA), suggesting that they are enteroendocrine cells. We demonstrate that the majority of the CgA/GPR84 cells are X/A-like ghrelin cells. The high degree of overlap between ghrelin and GPR84 decreased post-weaning, whereas the overlap between ghrelin and GPR120 increased. At the apical region of the glands the fatty acid receptors were mainly expressed in unique cell types. These contain lipid-filled vacuole- and vesicle-like structures and may have absorptive functions. We detected decreased immunoreactivity for GPR84 and no lipid droplets in surface cells post-weaning. In conclusion, expression of GPR84 in ghrelin cells as well as in surface cells suggests an important role of medium chain fatty acids in the developing gastric mucosa of suckling mice.